A mediação em sala de aula sob a perspectiva de Feuerstein: uma pesquisa-ação sobre a interação professor-aluno-objeto da aprendizagem - Pisacco, Nelba Maria Teixeira (2006)
The present work investigates the interaction in classroom, under the trine conception of the mediation of the learning. The object of the study is composed by the very mediation elements: pupils, teacher, and learning object. The research main target was to demonstrate how, under the perspective of Feuerstein, the interaction among mediator, mediated and learning object is processed. Specifically, the proposal is: to characterize the relationships that occur between the constituent elements of the mediation and the mediational criteria; to demonstrate how the mediation criteria occurs in the teaching and learning process; and to identify the possibilities and impediments in the planning and accomplishment of the classes under the parameters of the moderated activity experience. The theoretical reference is based in Reuven Feuerstein's theoretical-instrumental proposal, particularly on the concerns of the mediated learning experience (MLE) – conceived as a process of mediated intentions that promote the structural cognitive modifiability (SCM) – and of the mediation criteria, that constitute the basic condition for characterization of the mediation. The methodology proposes the observation of the educational practices of mediation, according to the mediational categories, to be evaluated either by the pupils as by the teacher in classroom. In a research-action idea, the teacher and the twenty-five students – of the Normal Course, at a private school in the city of Ponta Grossa (state of Parana, Brazil) – became subject/object of the research, in the sense of the mediational actions evaluation. As instruments, the following were used: class plans, teacher's diary notes and recordings, teacher's and students’ records protocols, video-recording and questionnaires. The analysis and discussion were constituted in the interlacement of quantitative and qualitative indicators. The conclusion was that the interaction mediator-moderated – object of the learning, took place in different ways. The variables that interfere in such distinctions refer to: the cognitive and subjective aspects of the mediator and of the moderated ones, the specificities of the learning object, the didactic-methodological strategies, time, space, the moment lived by the group, and the differences of each criterion. From the interaction between each criterion and the elements of the mediation, some unilateral, bilateral and trine relationships emerged, which demonstrated the differentiation of the actions promoters of the mediation of each criterion. The occurrence of all of the criteria, with different frequencies, superior indexes for the criteria of mediation of the meaning, of the behavior of sharing, and of the intentionality/reciprocity, was observed. The mediational criteria are interdependent; the closest link was observed between the mediation of meaning, and the mediation of transcendence; however, the mediation of all of the criteria was permeated from those which are considered universal and fundamental parameters for the occurrence of the MLE: the intentionality/reciprocity mediation, the mediation of meaning, and the mediation of transcendence. The mediation is a two-way road: in the same class, each individual goes thru different processes of interaction and subjectivity, he attributes a self sense to a certain same lived social situation, and he constitutes his autonomy and identity as subject of the learning. Despite the distinct interactions, the indicators denote that the richness of the interaction enabled progresses, and the use of the parameters as advisors of the class favored the MLE in the school context. So, learning and teaching rendered being inseparable actions for mediators and mediated.